2020
DOI: 10.1021/acs.jctc.9b01215
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Density Fitting with Modified Cholesky Decomposition Applied to Second-Order Electron Propagator

Abstract: Computation of molecular orbital electron repulsion integrals (MO-ERIs) as a transformation from atomic orbital ERIs (AO-ERIs) is the bottleneck of second-order electron propagator calculations when a single orbital is studied. In this contribution, asymmetric density fitting is combined with modified Cholesky decomposition to generate efficiently the required MO-ERIs. The key point of the presented algorithms is to keep track of integrals through partial contractions performed on three-center AO-ERIs; these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In parallel with the work of Folkestad et al, Lew‐Yee et al 68 reported two algorithms on the combination of asymmetric DF together with CD ERIs in a second‐order propagator implementation. Most recently, Zhang et al 69 reported a careful analysis of the computational costs of the two‐step procedure, and determined the optimal way to implement CD with respect to memory footprint and number of floating‐point operations.…”
Section: Cholesky Decompositionsmentioning
confidence: 99%
“…In parallel with the work of Folkestad et al, Lew‐Yee et al 68 reported two algorithms on the combination of asymmetric DF together with CD ERIs in a second‐order propagator implementation. Most recently, Zhang et al 69 reported a careful analysis of the computational costs of the two‐step procedure, and determined the optimal way to implement CD with respect to memory footprint and number of floating‐point operations.…”
Section: Cholesky Decompositionsmentioning
confidence: 99%
“…In the authors’ experience, AZD3 makes it feasible to compute systems 1 order of magnitude bigger than those viable with PP2. Analysis of the formal scaling and timings for the second-order propagator and ADPT can be found in recent reports. , Systems with around 1000 atoms have been treated with ADPT. , …”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the formal scaling and timings for the second-order propagator and ADPT can be found in recent reports. 29,58 Systems with around 1000 atoms have been treated with ADPT. 29,32 Connection with the h Function.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Folkestad et al 67 have used this procedure in e T in CCSD calculations on systems with up to 80 000 AO basis functions, see fig. In parallel with the work of Folkestad et al, Lew-Yee et al 68 reported two algorithms on the combination of asymmetric DF together with CD ERIs in a second-order propagator implementation. Most recently, Zhang et al 69 reported a careful analysis of the computational costs of the two-step procedure, determining the optimal way to implement CD with respect to memory footprint and number of floatingpoint operations.…”
Section: Literature Reviewmentioning
confidence: 99%